2008
DOI: 10.1080/09603120802272193
|View full text |Cite
|
Sign up to set email alerts
|

Food hygiene training in small to medium-sized care settings

Abstract: Adoption of safe food handling practices is essential to effectively manage food safety. This study explores the impact of basic or foundation level food hygiene training on the attitudes and intentions of food handlers (n=135) in small/medium sized care settings, using questionnaires based on The Theory of Planned Behaviour.Interviews were also conducted with food handlers (n=20) and their managers (n=10) to ascertain beliefs about the efficacy of, perceived barriers to and relevance of training.Most food han… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 20 publications
0
19
0
1
Order By: Relevance
“…Despite an increase in the number of food handlers receiving such training, a high proportion of food poisoning outbreaks still occur in commercial catering settings as a result of poor food handling practices (Clayton, Griffith, Price, & Peters, 2002). The enactment of safe food handling practices, learnt during food hygiene training, requires the food handler to use the resources available to them and implement the knowledge and skills into practical application, unfortunately, in most cases, food hygiene training does not translate into positive food handling behaviours (Clayton et al, 2002;Green et al, 2005;Powell, Attwell, & Massey, 1997;Riben, Mathias, Campbell, & Wiens, 1994) or any behavioural changes which are noticed in the workplace are ephemeral (Seaman & Eves, 2008). Although many reports (Little, Lock, Barnes, & Mitchell, 2003;Rennie, 1994;Worsfold, Griffith, & Worsfold, 2004) indicate the failure of formal courses to generate improvements in food handling practices, investigators almost invariably concluded that food hygiene education programmes should be encouraged.…”
Section: Introductionmentioning
confidence: 95%
“…Despite an increase in the number of food handlers receiving such training, a high proportion of food poisoning outbreaks still occur in commercial catering settings as a result of poor food handling practices (Clayton, Griffith, Price, & Peters, 2002). The enactment of safe food handling practices, learnt during food hygiene training, requires the food handler to use the resources available to them and implement the knowledge and skills into practical application, unfortunately, in most cases, food hygiene training does not translate into positive food handling behaviours (Clayton et al, 2002;Green et al, 2005;Powell, Attwell, & Massey, 1997;Riben, Mathias, Campbell, & Wiens, 1994) or any behavioural changes which are noticed in the workplace are ephemeral (Seaman & Eves, 2008). Although many reports (Little, Lock, Barnes, & Mitchell, 2003;Rennie, 1994;Worsfold, Griffith, & Worsfold, 2004) indicate the failure of formal courses to generate improvements in food handling practices, investigators almost invariably concluded that food hygiene education programmes should be encouraged.…”
Section: Introductionmentioning
confidence: 95%
“…Training and education are essential to ensure that workers have the awareness and knowledge necessary to comply with food hygiene demands, although these do not always result in a positive change in food handling behavior (Clayton, Griffith, Price & Peters, 2002;Seaman & Eves, 2008). The need for training of food handlers is an essential part of HACCP concept and is thus recognized by EU legislation (EU Regulation 852/2004) and by international organizations such as the WHO (WHO, 2000).…”
Section: Introductionmentioning
confidence: 98%
“…Offering a safe meal for these individuals is very important, and a systematic approach is required to control food contaminants. This approach includes implementing tools to preserve the hygienicsanitary quality of foods, updating knowledge and perceptions, and supervising the technical staff members responsible for identifying factors that may contribute to the development of the foodborne diseases (BUCCHERI et al, 2007;EVES, 2008;SOUSA;CAMPOS, 2003).…”
Section: Introductionmentioning
confidence: 99%